HOW DO ONLINE STUDENTS DIFFER FROM LECTURE STUDENTS? - John Dutton; Marilyn Dutton; Jo Perry (Online Learning, 2019)
This study has two primary objectives. First, we want to know how students who enroll in online classes differ from their peers in traditional lecture classes. Our second objective involves both exploring what factors influence performance among online students, as well as whether those factors differ for online and lecture students. Our comparisons are of two large sections of a course in computer programming for which almost the only difference was that one section consisted of on-campus lectures, and the other section was online. We find that online students do differ from lecture students in a number of important characteristics. However, when we examine class performance and course completion, we find that the factors which influence performance seem to have a stronger impact on lecture students, but we cannot reject the hypothesis that factor coefficients are the same for the two groups.